Magnetopause MHD surface wave theory: progress & challenges - Archer, Martin O.; Pilipenko, Vyacheslav A.; Li, Bo; Sorathia, Kareem; Nakariakov, Valery M.; Elsden, Tom; Nykyri, Katariina (Frontiers in Astronomy and Space Sciences, 2024)
Sharp boundaries are a key feature of space plasma environments universally, with their wave-like motion (driven by pressure variations or flow shears) playing a key role in mass, momentum, and energy transfer. This review summarises magnetohydrodynamic surface wave theory with particular reference to Earth’s magnetopause, due to its mediation of the solar-terrestrial interaction. Basic analytic theory of propagating and standing surface waves within simple models are presented, highlighting many of the typically-used assumptions. We raise several conceptual challenges to understanding the nature of surface waves within a complex environment such as a magnetosphere, including the effects of magnetic topology and curvilinear geometry, plasma inhomogeneity, finite boundary width, the presence of multiple boundaries, turbulent driving, and wave nonlinearity. Approaches to gain physical insight into these challenges are suggested. We also discuss how global simulations have proven a fruitful tool in studying surface waves in more representative environments than analytic theory allows. Finally, we highlight strong interdisciplinary links with solar physics which might help the magnetospheric community. Ultimately several upcoming missions provide motivation for advancing magnetopause surface wave theory towards understanding their global role in filtering, accumulating, and guiding turbulent solar wind driving.